Busana Muslimah, Hukum Islam, dan Governmentality: Analisis Regulasi Moral atas Tubuh Perempuan di Ruang Publik - Edo Ferdian; Masdar Hilmy; Desi Erawati (Social Science Academic, 2026)
This research aims to analyze the phenomenon of Muslim women's fashion in the perspective of Islamic law and Michel Foucault's theory of governmentality. The focus of the study is directed at how Muslim women's clothing, especially the hijab, not only functions as an expression of personal religiosity, but also becomes an object of moral regulation, social discipline, and the formation of religious identity in public spaces. This research uses a qualitative approach with a type of literature research combined with socio-legal perspectives and critical social theory. Data were obtained from Islamic legal literature, maqāṣid al-syarī'ah, governmentality theory, and academic studies on hijab regulation, sharia formalization, and religious freedom. The results of the study show that Muslim women's clothing in Islamic law has a normative dimension as part of dress ethics, modesty, and honor guarding. However, in social practice, such norms can shift into control mechanisms when institutionalized through policies, institutional pressures, or enforced standards of piety. The governmentality perspective explains that the regulation of Muslim women's clothing works through the normalization, supervision, and formation of pious female subjects who obey certain moral standards. This study concludes that the regulation of Muslim women's clothing needs to be placed within the framework of maqāṣid al-shari'ah so that it does not stop at symbolic control, but remains oriented towards justice, welfare, religious freedom, and respect for women's dignity.